If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + 5 = 8d + 2 Reorder the terms: 5 + 2d = 8d + 2 Reorder the terms: 5 + 2d = 2 + 8d Solving 5 + 2d = 2 + 8d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-8d' to each side of the equation. 5 + 2d + -8d = 2 + 8d + -8d Combine like terms: 2d + -8d = -6d 5 + -6d = 2 + 8d + -8d Combine like terms: 8d + -8d = 0 5 + -6d = 2 + 0 5 + -6d = 2 Add '-5' to each side of the equation. 5 + -5 + -6d = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -6d = 2 + -5 -6d = 2 + -5 Combine like terms: 2 + -5 = -3 -6d = -3 Divide each side by '-6'. d = 0.5 Simplifying d = 0.5
| 2(x+4)=0 | | j+-1=-2 | | -(5w+u)+3(3u+3w)= | | 4(x-7)=-32 | | ar+2=3R-6t | | 9=0.5*4h+1 | | 2(x+7)=24 | | e+-3=7 | | -6+d=2 | | 2y(x+5)=4w | | 18=-6(p+5) | | -17+c=-13 | | 9=4h+1 | | b+2=-6 | | -5+a=-15 | | 2x-11y=3 | | x+2x+3x+4x+5x=45 | | 3x+5+12=4 | | 2x^2=6x-16 | | x^2=2x+5.5 | | a=2l^2-5l | | 15x-39=27x-74 | | 16x-33=14x-29 | | 16x-33=16x-39 | | 9p-20=-2+6p | | 7.3*3.4= | | 14x+-1=29x+44 | | 9s-9=-6+6s | | 8x+8=9x+4 | | a+(a-2)=(a+3)-(a+1) | | 8x+5=7x | | 8n-5=43 |